PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POWTOON TERHADAP PEMAHAMAN SISWA KELAS VI PADA MATERI WAWANCARA BAHASA SUNDA - Iqna Nafilatul Faujiyah; Akhmad Nugraha; Dwi Alia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of powtoon media on the understanding of class VI students. This type of research is quantitative, non-equivalent control group design, quasi-experimental type. The population in this study was all two classes of VI class with a total of 40 students. The sampling technique used by researchers is a non-probability sampling technique with a saturated sampling technique. . The data collection techniques used are tests, questionnaires and documentation. The research results showed that the average pretest for the experimental class was 56.00 and the pretest for the control class was 59.00. The average posttest for the experimental class was 77.50, while the average posttest for the control class was 66.50. Hypothesis testing using the Paired Sample T-test shows Sig (2-tailed) < 0.005 (0.000 < 0.05) which means Ho is rejected and Ha is accepted. In the N-Gain test for the experimental class it was 0.435 in the